On Music, Order, and Memory: Investigating Augustine’s Descriptive Method in the Confessions - Wiskus Jessica (Open Theology, 2020)
Augustine’s account in the Confessions Book IX of his ecstasy at Ostia remains unsurpassed in its poetic force, yet unusual, as a description of religious experience, in two particular respects. First of all, what he describes is not a “vision” of God, but an experience of listening. Second, it is not a solitary but a shared experience (e.g., with his mother, Monica). This essay considers the significance of these two elements by analyzing the relation between his description in Book IX and the understanding of rhythm that he develops in De musica. Drawing also on Book X (on memory) and Book XI (on time-consciousness) in the Confessions, I investigate a particular type of flowing memory – what I call, “perfect” memory – that characterizes the temporally ordered movements of musical rhythm, showing that it is in this type of memory that Augustine finds God.